The Interpretation of the Meaning of al-Qarábah in the Qur'an and Its Contextualization with Contemporary Kinship Models (An Interpretative Approach Using the Maudhu'i Tafsir Method): Interpretasi Makna al-Qarábah dalam al-Qur’an dan Kontekstualisasinya dengan Model Kerabat Era Kontemporer (Pendekatan Intepretatif dengan Metode Tafsir Maudhu‘i) - Bakry, Nurdin; Sulfanwandi, Sulfanwandi; Habibi MZ, Muhammad (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
Based on the interpretation in the Qur'an, relatives (al-qurbá) are interpreted flexibly, according to the context of the conversation, both from the side of the mother's and father's relatives. However, traditional interpretations tend to emphasize the paternal family, reflected in the influence of patrilineal Arabic culture. In the contemporary era, the concept of family in anthropology has varied, including maternal or bilateral models. This study analyzes how the meaning of al-qarábah in the Qur'an with the approach of maudhu'i tafsir, tracing its conformity with the contemporary kinship model? The type of qualitative research and interpretive approach is carried out in order to be answered in depth, data collection through library research, so that the data collected is in the form of secondary data obtained from the books of scholarly interpretation. Content analysis is carried out by collecting verses related to the method of tafsir maudhu'i. As a result, the method of tafsir maudhu'i al-qarābah in Islam is divided into three levels: al-qarābah al-qarībah (very close uterine relationship), al-qarābah al-mutawassiṭah (mahram relatives), and al-qarābah al-baʿidah (non-mahram relatives). In the context of the modern family, kinship is understood through the biological dimensions (nasab/DNA), religion (brothers and sisters), and social (neighborly relationships). Fathers and mothers are considered the nucleus of the family in Islam, with mothers having primary responsibility for the upbringing, education, and inheritance of children in the event of a father's death, affirming protection and harmony in Muslim families.